Quality of Life Among Secondary School Teachers in Kwara State: Implication for Counselling - Kamaldeen, Rahmat Tinuke; Tiamiyu, Kamoru Abidoye; Ogo-Oluwa, Ameenat Arinola (ASEAN Journal of Educational Research and Technology, 2024)
Teachers are one of the most valuable human resources in a school system. The strengths and quality of any educational system are heavily reliant on the efforts of its teachers. It is commonly known that teaching is one of the most stressful jobs in the world. Teachers tend to view aspects of their profession that are hazardous to their health. The school system in Kwara State has lately experienced significant modifications. Nonetheless, despite numerous reforms and advances over the years, Kwara teachers continue to face stressful working conditions when compared to other jobs. Numerous studies have demonstrated that teachers’ physical and mental health might suffer as a result of excessive stress. It has been claimed that teachers who have a lower quality of life live shorter lives. School teachers must have a high quality of life to train good students. Any fault or flaw in teachers' quality of life might have an impact on their job performance. As a result, the purpose of this study is to look at teachers' quality of life in Kwara State secondary schools, as well as the consequences of counselling. As a result, the report proposed instructors be provided additional assistance in improving their quality of life and well-being.